Neuropsychiatric expression and catatonia in 22q11.2 deletion syndrome: An overview and case series. Issue 10 (19th May 2018) - Butcher, Nancy J.; Boot, Erik; Lang, Anthony E.; Andrade, Danielle; Vorstman, Jacob; McDonald‐McGinn, Donna; Bassett, Anne S.
Abstract : Individuals with 22q11.2 deletion syndrome (22q11.2DS) are at elevated risk of developing treatable psychiatric and neurological disorders, including anxiety disorders, schizophrenia, seizures, and movement disorders, often beginning in adolescence or early to mid‐adulthood. Here, we provide an overview of neuropsychiatric features associated with 22q11.2DS in adulthood. Results of a new case series of 13 individuals with 22q11.2DS and catatonic features together with 5 previously reported cases support a potential association of this serious psychomotor phenotype with the 22q11.2 deletion. As in the general population, catatonic features in 22q11.2DS occurred in individuals with schizophrenia, other psychotic and non‐psychotic psychiatric disorders, and neurological disorders like Parkinson's disease. We place the results in the context of an updated review of catatonia in other genetic conditions. The complex neuropsychiatric expression and risk profile of 22q11.2DS highlights the need to consider co‐morbid factors and provide care tailored to the individual patient. The results reinforce the need for periodic monitoring for the emergence of psychiatric and neurological manifestations including catatonic features. Pending further research, enhanced recognition and informed anticipatory care promise to facilitate the early diagnosis that allows for timely implementation and optimization of effective treatments.